Chief Minister's Comprehensive Health Insurance Scheme Tamil Nadu (CMCHISTN) tool towards Universal Health Coverage (UHC) in Tamil Nadu, India - T S Selvavinayagam (Wolters Kluwer Medknow Publications, 2017)
Background: The state of Tamil Nadu in India is one of the states with better health indicators in the country. With an ambition to provide still better health care to the residents of the state, the possibilities of the journey towards UHC are analyzed. Objectives: To explore the possibilities of using the existing Chief Minister's Comprehensive Health Insurance Scheme (CMCHISTN) as base to reach Universal Health Coverage (UHC) in Tamil Nadu. Methods: The various dimensions of UHC namely people, benefit, and financial protection are analyzed considering the present status in the state particularly the Chief Minister's Comprehensive Health Insurance Scheme and matched with future needs to reach UHC in Tamil Nadu. This provides the vital indications in success towards UHC. Results and conclusion: The gap between the existing modalities under CMCHSITN and requirements for UHC are within the reachable level. With additional resources and effort, it is possible to reach UHC in Tamil Nadu in the near future. CMCHISTN is one of the best available options for reaching UHC in Tamil Nadu.